If The Shoe Fits - Mlynowski, Sarah (New York, New York Scholastic Inc., 2013)
On their second adventure through the magic mirror Abby and Jonah find themselves in the Cinderella fairy tale--and that is when things start to go really wrong.
Booklist
Horn Book
School Library Journal
Booklist, January 2013
Horn Book, November 2013
Kirkus Review, November 2012
Keywords: Brothers and sisters -- Fiction; Brothers and sisters -- Juvenile fiction; Cinderella (Legendary character) -- Juvenile fiction; Magic mirrors -- Juvenile fiction; Brothers and sisters -- Fiction; Characters in literature -- Fiction; Characters and characteristics in literature -- Fiction; Cinderella (Legendary character) -- Fiction; Fairy tales; Magic -- Fiction; Siblings -- Fiction; Siblings -- Juvenile fiction